Risk Factors Associated With Cephalomedullary Nail Cutout in the Treatment of Trochanteric Hip Fractures. Issue 11 (November 2017) - Ciufo, David J.; Zaruta, Douglas A.; Lipof, Jason S.; Judd, Kyle T.; Gorczyca, John T.; Ketz, John P.
Abstract : Objectives: To evaluate the association of cephalomedullary nail cutout in trochanteric femur fractures with the presence of the following radiographic variables: lateral wall fracture, posteromedial fragment, angular malreduction, residual basicervical fracture gapping, screw placement, and tip–apex distance. Design: Retrospective review. Setting: Academic medical center. Patients: A total of 362 patients were included in the study. The average age was 83 years and the majority was female. All sustained low-energy trochanteric femur fractures treated operatively with cephalomedullary nails. Minimum radiographic follow-up was 3 months, with an average of 11 (range 3–88) months. Intervention: Cephalomedullary nailing with either a lag screw or helical blade. Main Outcome Measures: Cutout of the lag screw or helical blade. Results: A total of 22 (6%) cutouts occurred. Univariate analysis showed significantly ( P ⩽ 0.01) more frequent cutout with fracture of the lateral wall, posteromedial fragment, residual gapping (>3 mm) at basicervical component, neck–shaft malreduction >5 degrees varus or 15 degrees valgus, and tip–apex distance >25 mm, and superior screw/blade positioning. There was no difference with unstable fracture pattern ( P = 0.58) or fellowship training ( P = 0.21). Multivariate regression analysis demonstrates that lateral wall fracture (Odds ratios [OR] = 8.0, 95% confidence interval [CI], 2.4–27.1), neck–shaft malreduction (OR = 4.3, CI, 1.3–14.7), and residual basicervical gapping (OR = 3.6, CI, 1.0–13.0) were associated with fixation cutout. Conclusions: Risk factors for cutout of trochanteric fractures in our study can be viewed as modifiable or nonmodifiable factors. Statistically significant factors included lateral wall fracture (nonmodifiable) as well as basicervical gapping and malreduction (modifiable). Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.